Identification of Diet with Anemia Incidence in Pregnant Women in the Working Area of Puuwatu Health Center - Milana Milana; Mien Mien; Siti Umrana (KLASICS, 2023)
Anemia is a health problem that is experienced by many pregnant women and can cause problems for both the mother and the baby she is carrying. Anemia in pregnant women not only affects the growth and development of the fetus, but also causes placental disorders such as hypertrophy and infarction that interfere with function. The purpose of this study was to determine the relationship between the prevalence of anemia in the working area of ​​the Puuwatu Health Center and eating habits. This study used a quantitative research design with a descriptive approach and a purposive sampling strategy. The population in this study were pregnant women in the working area of ​​the Puuwatu Wellbeing Center with a total of 41 respondents. Based on the findings of anemic pregnant women, there were 26 (61.9%) anemic pregnant women whose diet was poor, and there were 15 (35.7%) anemic pregnant women whose diet was good. Based on the research findings, it can be concluded that the majority of pre-pregnant women. A small proportion of respondents had bad eating patterns, namely 26 people (61.9 percent), while only a small number of respondents had good eating patterns, namely 15 people (35.7 percent)